Helminth infection and eosinophilia and the risk of Plasmodium falciparum malaria in 1- to 6-year-old children in a malaria endemic area. - Philip Bejon; Tabitha W Mwangi; Brett Lowe; Norbert Peshu; Adrian V S Hill; Kevin Marsh (PLoS Neglected Tropical Diseases, 2008)
Helminth infection is common in malaria endemic areas, and an interaction between the two would be of considerable public health importance. Animal models suggest that helminth infections may increase susceptibility to malaria, but epidemiological data has been limited and contradictory.In a vaccine trial, we studied 387 one- to six-year-old children for the effect of helminth infections on febrile Plasmodium falciparum malaria episodes. Gastrointestinal helminth infection and eosinophilia were prevalent (25% and 50% respectively), but did not influence susceptibility to malaria. Hazard ratios were 1 for gastrointestinal helminth infection (95% CI 0.6-1.6) and 0.85 and 0.85 for mild and marked eosinophilia, respectively (95% CI 0.56-1.76 and 0.69-1.96). Incident rate ratios for multiple episodes were 0.83 for gastro-intestinal helminth infection (95% CI 0.5-1.33) and 0.86 and 0.98 for mild and marked eosinophilia (95% CI 0.5-1.4 and 0.6-1.5).There was no evidence that infection with gastrointestinal helminths or urinary schistosomiasis increased susceptibility to Plasmodium falciparum malaria in this study. Larger studies including populations with a greater prevalence of helminth infection should be undertaken.